Co-Pyrolysis of Lignite and Oil Plant Cake Blends - Yilgin, Melek (Jihad Daneshgahi, 2022)
Although today's fossil fuel reserves have been still considered a long-term energy supply, biomass has received worldwide attention as a cheap and renewable energy source due to the known global environmental impact of fossil fuel usage. Then co-processing of fossil fuels and biomasses to produce substitute liquid fuels is one option to appraise fossil fuel reserves for the economy. In this work, pyrolysis of Soma lignite and an oil plant cake, and their blends of varied proportions in the form of pellets were studied to elucidate the main differences between the behavior of these materials and their blends during fast thermal decomposition carried to convert their valuable products. A special vertical heating chamber, which enabled very fast heating, was used in the experiments conducted at 500- 700 degrees C temperature range. The results showed that these two materials mutually interacted when the cake ratios of the pellets were below 50%. For blends with 75% cake, some interaction was observed only at 700 degrees C. It is concluded that the interaction between two materials during pyrolysis is affected by the outflow rates of volatiles into the sweeping gas. Maximum liquid yields corresponded to blends containing OPC greater than 75%.
Keywords: Lignite; Oil plant cake; Co-pyrolysis; Synergistic effect